Iket âKi Mas Jongâ Dan Representasi Identitas Banten - Priana, Ronny Yudhi Septa (Jurnal Riset Komunikasi, 2017)
Cultural representations of a society can be demonstrated through the symbols used on dress and other cultural products. This not point out of how to the efforts of everyone who read and interpret the symbolism of an object. This research tries to unravel by signs on the body in the form of a bond head with a two significance Roland Barthes. This study uses qualitative descriptive method using semiotic analysis of Roland Barthes. The research data is in the form of iket âKi Mas Jongâ which is a symbol of culture of Banten Province. research shows that there are meanings denotation and connotation that represent the culture of the community. Understanding symbols can be seen and assessed by the reading of meaning through mythical significance.